UV Signature Mutations Reclassify Salivary High-grade Neuroendocrine Carcinomas as Occult Metastatic Cutaneous Merkel Cell Carcinomas. (May 2019) - Sun, Lulu; Cliften, Paul F.; Duncavage, Eric J.; Lewis, James S.; Chernock, Rebecca D.
Abstract : Salivary high-grade neuroendocrine carcinomas (NECs) are rare, occur predominantly in the parotid gland, and are difficult to differentiate from metastatic cutaneous Merkel cell carcinomas (MCCs), which have overlapping morphologic, immunophenotypic, and molecular profiles. Oncogenic Merkel cell polyomavirus (MCPyV), found in 70% to 80% of MCCs, has also been reported in a few salivary NECs, but this is controversial. A promising biomarker to distinguish the 2 tumor types are UV signature mutations. UV signature mutations indicate a sun damage-induced mechanism of pathogenesis and recently have been found to be highly prevalent in MCPyV-negative MCCs but would be inconsistent with salivary origin. Here, we examine UV signature mutations as a molecular marker to distinguish primary salivary high-grade NEC from MCC. Whole exome DNA sequencing was performed on matched tumor-normal tissue from 4 MCPyV-negative high-grade salivary NECs with no other primary source identified, as well as 3 melanomas and 3 lung NECs as positive and negative controls, respectively. UV signature mutations were found in all salivary NECs, when defined as ≥60% of total mutations being C-to-T transitions at dipyrimidine sites, and when compared with known human cancer-related mutational signatures. The presence of UV signature mutations in salivary high-grade NECs strongly favors these to be occult metastatic MCCs. True salivary primary NECs are likely exceedingly rare. When a high-grade NEC is encountered in the salivary gland, the presence of UV signature mutations or MCPyV may be useful to exclude occult unknown primary MCC. Abstract : Supplemental Digital Content is available in the text.